The Reactive Deposition of TiO[x] Thin Films; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Sidelev D. V. Dmitry Vladimirovich (Technologies of Electrophysical Methods of Materials Treatment, 2014)
Title screen